The Application of Concept of Social Capital in the Study of Crime - Bilinović, Ana; Tripković, Gordana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2013)
This paper analyzes the effects of different components of social capital (social networks, cooperative norms, informal sanctions and trust) on criminal activity. Specificity of relationshipbetween social capital and crime is presented on individual – micro level, by analysing the nature of social capital of offenders and victims; meso level, by analyzing the social context and environmental context within which crime is taking place, and finally, at the macro level, where attention is paid to regional and national differences in social capital and its impact on crime rates. Positive effects and the role of social networks in preventing crime are represented, among others, by the index of "collective efficacy" and the "neighbourhood watch". Special attention is paid to "negative" social capital, specifically the "criminal capital", which focuses on the deviant social network.